2014
DOI: 10.1007/s00339-014-8749-9
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of Yb3+/Ho3+ co-doped air cladding silica-based fiber fabricated with plasma non-chemical vapor deposition method

Abstract: In this paper, the fibers with Yb 3? /Ho 3? codoped air cladding are fabricated by the plasma nonchemical vapor deposition method with the stack-capillarydraw technique for the first time to our knowledge. By the excitation at 975 nm, the fluorescence and up-conversion emission properties of these fibers are experimentally investigated. The mechanism of up-conversion emission is analyzed. The results show that such a fiber fabricated by using the plasma non-chemical vapor deposition method can be used as the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 24 publications
(14 reference statements)
0
9
0
Order By: Relevance
“…The presence of Yb 3+ ions in the Ho 3+ -doped ZnGa 2 O 4 phosphor can be used to increase the UC emission intensity considerably. [16][17][18][19][20]27,31 Moreover, when the Li + ion is also present in the Ho 3+ /Yb 3+ co-doped phosphors, the UC emission intensity of the phosphor can be further increased significantly. 7,14,22,24−26 It has been observed that the UC emission intensity of the Ho 3+ /Yb 3+ co-doped phosphor was examined to increase considerably in the presence of Li + ions in different host materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of Yb 3+ ions in the Ho 3+ -doped ZnGa 2 O 4 phosphor can be used to increase the UC emission intensity considerably. [16][17][18][19][20]27,31 Moreover, when the Li + ion is also present in the Ho 3+ /Yb 3+ co-doped phosphors, the UC emission intensity of the phosphor can be further increased significantly. 7,14,22,24−26 It has been observed that the UC emission intensity of the Ho 3+ /Yb 3+ co-doped phosphor was examined to increase considerably in the presence of Li + ions in different host materials.…”
Section: Introductionmentioning
confidence: 99%
“…In this process, the absorption of two or more low energy photons leads to emission of high energy photons (i.e., anti-Stoke emission). Some of the triply ionized rare earth ions are a rich source of intense UC emission because of their favorable energy levels. The triply ionized rare earth-doped phosphor materials emitting intense, sharp, and narrow bandwidth emissions have potential applications in a variety of technological fields, such as blue-, green-, and red-emitting materials; optical heating; temperature sensing; bio-thermal treatment; bio-imaging; medical therapy; and so forth. The Ho 3+ ion is a rare earth ion that has huge number of energy states, and it is known for its emission from UV to NIR regions through different optical processes, such as UC, downconversion (DC), and quantum cutting (QC) emissions, and so forth. , The UC mechanisms in Ho 3+ /Yb 3+ co-doped phosphors were widely explored by many researchers in different combinations of surface enhancers and sensitizers. , Most of the sensitizers are optically opaque for the NIR radiations, which do not play any role in the UC process. ,, They only used to improve the local crystal structure of the phosphor samples. Therefore, the selection of a suitable surface enhancer is highly desired.…”
Section: Introductionmentioning
confidence: 99%
“…co-doped air cladding fiber preform is prepared by combining the high-temperature plasma furnace sintering technology and the dried RE-doped granulates (Xia et al 2015). This technology is selected because it can provide the large volume of heavily doped silica glass (Xia et al 2015). In addition, the dried RE-doped granulates in this process is obtained by the hydrolysis of SiCl 4 in the RE-doped and co-doped ions solution, which can provide the homogenous of the core RI distribution.…”
Section: Methodsmentioning
confidence: 99%
“…/Al 3? co-doped air cladding fiber preform is prepared by combining the high-temperature plasma furnace sintering technology and the dried RE-doped granulates (Xia et al 2015). This technology is selected because it can provide the large volume of heavily doped silica glass (Xia et al 2015).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation